Longitudinal Analysis of Erythrocyte and Plasma Protoporphyrin Levels in Patients with Protoporphyria. (1st September 2018) - Gou, Eric; Weng, Cindy; Greene, Tom; Anderson, Karl E; Phillips, John D
Abstract: Background: Erythropoietic protoporphyria (EPP) and X-linked protoporphyria (XLP) are inherited cutaneous porphyrias resulting from decreased activity of ferrochelatase and gain-of-function mutations of δ-aminolevulinic acid synthase-2, respectively. Both of these protoporphyrias cause increased protoporphyrin levels that cause photosensitivity and may lead to hepatopathy and further increases in erythrocyte and plasma porphyrin levels. Methods: We evaluated erythrocyte protoporphyrin and plasma porphyrin levels in all subjects with EPP (83 subjects) or XLP (9 subjects) without evidence of liver disease tested repeatedly at a single laboratory over 25 years. Results: Intersubject variation contributed more than intrasubject variation (78.86% vs 21.14%) to overall variability, and longitudinal variability, estimated by CV, averaged 26%. Erythrocyte total protoporphyrin levels were similar in males and females with EPP (ratio, 0.99; 95% CI, 0.82–1.21; P = 0.96) but were higher in males than females with XLP, although this difference was not statistically significant (ratio, 0.76; 95% CI, 0.43–1.36; P = 0.35). Analysis of 20 subjects from 9 separate families showed significant effects of family compared with effects of individual variation on total variance (50% vs 25%; P < 0.0001). Conclusion: Variation of erythrocyte total protoporphyrin up to 25% is expected in patients with protoporphyria, whereas greater increases might raise concern for protoporphyric hepatopathy.